Tracking Career Paths of Women in Neurosurgery. Issue 4 (16th May 2017) - Renfrow, Jaclyn J; Rodriguez, Analiz; Wilson, Taylor A; Germano, Isabelle M; Abosch, Aviva; Wolfe, Stacey Quintero
Abstract: BACKGROUND: Women represent a growing cohort of US neurosurgeons. OBJECTIVE: To describe postresidency fellowship, practice environment, and updated academic rank among female neurosurgeons. METHODS: Databases from the American Association of Neurological Surgeons (AANS) and the American Board of Neurological Surgery (ABNS) from 1964 to 2013 were reviewed for female neurosurgery residency graduates. Data on postresidency fellowships, practice environment (private vs academic), academic rank, board certification, and AANS/CNS (Congress of Neurological Surgeons) Joint Section on Women in Neurosurgery (WINS) membership were collected in 2016. Academic rank was verified from program websites and electronic correspondence. Faculty members were asked to report directorships and tenure. The AANS/CNS Joint Section on Women in Neurosurgery verified WINS membership. RESULTS: A total of 379 female neurosurgery residency graduates were identified in this 50-yr span. Of these, 70% became ABNS certified, and 2.1% left neurosurgery. Twenty-seven percent of women (n = 103) pursued fellowships, with pediatric neurosurgery (33%) the most common. Regarding practice environment, 26% entered academic medicine (n = 91), with 42 at the rank of assistant professor, 33 at the rank of associate professor, and 16 reaching the rank of full professor. CONCLUSION: Upon completion of training, 27% of women pursue fellowships. The distribution of women in private vs academic practice environments is proportionate to male neurosurgeons; however, the number women in academic leadership positions remains exceedingly low, with disproportionate representation in higher academic ranks. Women in national organized neurosurgery are increasing. Tracking the career paths of women in neurosurgery is a necessary step to identifying current achievements and opportunities for future progress.